Synthesis and biological evaluation of some new 1,3,4-thiadiazole and 1,2,4-triazole derivatives from L-methionine as antituberculosis and antiviral agents - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2015)
Some novel 1,3,4-thiadiazole [5-8] and 1,2,4-triazole [9-12] derivatives carrying amino acid moiety were synthesized starting from L-methionine. 1,3,4-Thiadiazole and 1,2,4-triazole scaffolds were prepared by cyclocondensation of the corresponding thiosemicarbazide and finally converted to their thiourea derivatives. Structures of the synthesized compounds [4-12] were confirmed by IR, H-1-NMR and C-13-NMR spectral data and elemental analysis. Synthesized compounds were evaluated for their antiviral and antibacterial activity. Of the screened compounds, N-{3-(methylsulfanyl)1-[5-(phenylamino)-1,3,4-thiadiazole-2-yl] propyl} benzamide 5] was identified as the most potent inhibitor of Influenza A H3N2 virus with an EC50 value of 31.4 mu M, which serves as a lead compound for prospective development. The antituberculosis activity screen of the synthesized compounds revealed 1-[4-(4-chloro-(3-trifluoromethyl) phenyl]-3-[3-(methylsulfanyl)- 1-(4-phenyl-5-thioxo-4,5-dihydro-1H-1,2,4-triazole3- yl) propyl] thiourea [12] as the most active compound against M. tuberculosis H37Rv strain (MIC : 30.88 mu M) but the compound proved not selective.
Keywords: Thioureas; 1,3,4-thiadiazoles; 1,2,4-triazoles; antiviral activity; influenza; antituberculosis activity; HIV-1 REVERSE-TRANSCRIPTASE; HERPES-SIMPLEX-VIRUS; HUMAN-IMMUNODEFICIENCY-VIRUS; ANTIMYCOBACTERIAL ACTIVITY; IN-VITRO; THIOUREA COMPOUNDS; MYCOBACTERIUM-TUBERCULOSIS; NONNUCLEOSIDE INHIBITORS; ANTICANCER ACTIVITY; COLORIMETRIC ASSAY